Abortion Rate Following Chorionic Villous Sampling and Amniocentesis in Twin Pregnancies - Fatemeh Golshahi; Fatemeh Rahimi-Sharbaf; Mahbobeh Shirazi; Sara Saeedi; Athar Abdolrazagh Nejad; Sahar Garfami; Nafise Saedi; Jafar Golshahi; Zeynab Amiriarya; Narjes Tavakolikia; Behrokh Sahebdel (Journal of Family and Reproductive Health)
Objective: Amniocentesis and chorionic villus sampling (CVS) are the most widely used prenatal diagnostic methods. Despite their benefits, they can be associated with adverse pregnancy effects, but the exact prevalence of these complications especially in twin pregnancies is not exactly known. Therefore, the present study was conducted to determine post-amniocentesis or CVS complications in twin pregnancies. Materials and methods: This retrospective observational study was conducted on 187 pregnant women who underwent amniocentesis or CVS in the perinatology department of Yas Hospital affiliated with Tehran University of Medical Sciences from January 2011 to March 2020. All participants were evaluated with amniocentesis or CVS by an expert perinatologist. The study outcomes were considered as the occurrence of vaginal bleeding, rupture of the membranes, chorioamnionitis, and abortion. Results: The mean age of women was 33.5 ± 6.5 years. About 90 % of pregnant women underwent amniocentesis and the others underwent CVS. In 132 (70.6%) pregnant women, the most common indication for diagnostic prenatal tests was having high-risk first/second-trimester screening followed by abnormal ultrasound anomaly scan in 31 (16.6%) cases. It was also found that in 80 (42.8%) patients, the placenta site was in the anterior part and 65 (34.8%) in the posterior part. The diagnostic test results were normal in 170 (90.4%) cases, while trisomy 21 was detected in 13 (7%) cases and trisomy 13 in 4 (2.1%) cases. The rate of abortion following CVS or amniocentesis in twin pregnancies was 3.7%, which was not associated with the study variables. Conclusion: The results of the present study showed that the rate of miscarriage following amniocentesis and CVS in twin pregnancies is 3.7%. Therefore, reassuring the parents about the benefits of amniocentesis or CVS rather than their rare complications is necessary.